Implantación de un Sistema Contable en el Comecial del Señor Luis Anival Mena Vasquez de la Ciudad de Loja Periodo 01 de Enero al 31 de Marzo del 2016. - Quinde Gonzales, Carmen Maribel (2017)
The present research work entitled "THE IMPLEMENTATION OF AN ACCOUNTING SYSTEM IN THE COMMERCE OF LUIS ANIVAL MENA VASQUEZ OF THE CITY OF LOJA DURING THE PERIOD 01 JANUARY TO 31 MARCH 2016", was developed with the aim to know the economic and financial situation of this business through the application of the accounting process to obtain the Financial Statements under International Accounting Standards (IAS), in order to give solutions to its proprietor and he can make opportune decisions. The goals set for the implementation of this work, make mention to the physical establishment of the properties, values and obligations that has Commercial of LUIS ANIVAL MENA VASQUEZ, to determine the initial inventory and determine its balance, which has been handled through the Multiple Account System that allowed to know the quantity of existing products, was necessary to develop the manual plan and of accounts, according to the activity and economic movement of the commercial, run an accounting process which was established with the support documentation provided by the owner of the commercial, then developed the Initial Inventory, State of Initial Situation, Daily General, Greater General, and Balance of Verification to get the spreadsheet with its respective settings until get the presentation of the financial statements, it summarize the economic and financial activity of the commercial, the same that was established in its entirety, based on accounting principles that allowed know the real economic situation that had the company. Also, it was made auxiliary documents such as: of sale, purchases, accounts to receive, accounts to pay, cash book, book banks, rolls of payment etc., which allowed to obtain a detailed data of the economic 5 transactions that take place daily in the commercial and in the same way to maintain control of it. According to the gotten results, it is advisable to continue using this system due to the benefits that it represents for the company, being the obtained information truthful and reliable, in this way give better results and as well, facilitate an opportune knowledge of the economic situation of the business. .